The Impact of Smart Tourism Infrastructure and Smart Tourism Governance on Destination Competitiveness with Emphasis on the Mediating Role of Smart Tourism Innovation - Heydari, Sheyda; Bakhshi, Hamed; Zargham Borujeni, Hamid; Kamel Tabbakh, Seyed Reza (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2026)
Objective:  The objective of this study is to examine the effects of smart tourism infrastructure and smart tourism governance on destination competitiveness, with an emphasis on the mediating role of smart tourism innovation.Methods and Materials: This study adopts an applied research approach and employs a descriptive–survey design. The statistical population consists of managers, experts, and employees working in tourism companies in the city of Mashhad. A total of 351 respondents were selected using a non-probability convenience sampling method. Data were collected through a standardized questionnaire designed to measure smart tourism infrastructure, smart tourism governance, smart tourism innovation, and destination competitiveness. To analyze the data and test the research hypotheses, structural equation modeling based on the partial least squares approach (PLS-SEM) was used. Reliability and validity of the measurement model were assessed through Cronbach’s alpha, composite reliability, average variance extracted, and discriminant validity tests, followed by evaluation of the structural model using path coefficients, coefficients of determination, predictive relevance, and goodness-of-fit indices.Findings: The results indicate that smart tourism infrastructure has a positive and significant effect on smart tourism innovation and destination competitiveness. Smart tourism governance also shows a positive and significant effect on both smart tourism innovation and destination competitiveness. In addition, smart tourism innovation has a positive and significant effect on destination competitiveness. The mediation analysis confirms that smart tourism innovation plays a significant mediating role in the relationships between smart tourism infrastructure and destination competitiveness, as well as between smart tourism governance and destination competitiveness, indicating that part of the impact of infrastructure and governance on competitiveness is transmitted through innovation.Conclusion: The findings demonstrate that destination competitiveness in smart tourism contexts is strengthened through the combined effects of smart infrastructure, effective governance, and innovation, highlighting the central role of smart tourism innovation as a strategic mechanism linking technological and institutional capacities to competitive outcomes.